Aluminum bronze crystallization on deformed base during electron beam additive manufacturing - Nikonov, Anton Yu; Lychagin, Dmitry V.; Bibko, Artem A.; Novitskaya, Olga S. (Metals)
To obtain products by using additive manufacturing (AM) methods, it is necessary to take into account the features of the formed internal structure of the material. The internal structure depends on the 3D printing parameters. To predict it, it is effective to use computer modeling methods. For this purpose, using the example of aluminum bronze, the influence of the base structure and heat input during surfacing on the grain structure of the deposited layers was studied. To create numerical models, we used data obtained from electron backscatter diffraction (EBSD) analysis of samples. The heterogeneity of the formation of the structure in each selected zone is established, which indicates the heterogeneity of heat input in local areas of the material in one mode of surfacing. For typical cases of crystallization, modeling using the molecular dynamics (MD) method of crystallization processes with different heat inputs to the base with characteristics specified based on experimental data was carried out. It was established that the amount of heat input determines the degree of melting and the inherited defectiveness of growing crystals. The formation of misorientation boundaries and crystallization centers of new grains is determined by the conditions of joint growth of grains with given crystallographic parameters of the computational model. The grain structure obtained as a result of simulation is consistent with the experimentally observed structure of the samples.